2016
DOI: 10.1073/pnas.1605543113
|View full text |Cite
|
Sign up to set email alerts
|

Regulated large-scale nucleosome density patterns and precise nucleosome positioning correlate with V(D)J recombination

Abstract: We show that the physical distribution of nucleosomes at antigen receptor loci is subject to regulated cell type-specific and lineagespecific positioning and correlates with the accessibility of these gene segments to recombination. At the Ig heavy chain locus (IgH), a nucleosome in pro-B cells is generally positioned over each IgH variable (VH) coding segment, directly adjacent to the recombination signal sequence (RSS), placing the RSS in a position accessible to the recombination activating gene (RAG) recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 71 publications
4
17
1
Order By: Relevance
“…Our observation that, during HL-60/S4 differentiation, nucleosome loss and nucleosome gain affect gene expression asymmetrically (i.e., a clear association with nucleosome loss and a more complicated response to nucleosome gain) agrees with the concept that there are several different mechanisms by which nucleosome positioning can affect gene expression. Interestingly, these changes in nucleosome occupancy involve extended regions of one to several kb, which is different from previously considered single-nucleosome repositioning scenarios and parallels a similar effect recently found at the V(D)J recombination domains 48 The molecular mechanisms of the change of chromatin density in extended regions that we report here may be linked to chromatin compartmentalization in domains such as TADs (topologically associated domains), 49,50 which have been recently shown to be correlated with regions of differential chromatin accessibility 51 . An exploration of this idea may provide a direction for new studies.…”
Section: Discussioncontrasting
confidence: 65%
“…Our observation that, during HL-60/S4 differentiation, nucleosome loss and nucleosome gain affect gene expression asymmetrically (i.e., a clear association with nucleosome loss and a more complicated response to nucleosome gain) agrees with the concept that there are several different mechanisms by which nucleosome positioning can affect gene expression. Interestingly, these changes in nucleosome occupancy involve extended regions of one to several kb, which is different from previously considered single-nucleosome repositioning scenarios and parallels a similar effect recently found at the V(D)J recombination domains 48 The molecular mechanisms of the change of chromatin density in extended regions that we report here may be linked to chromatin compartmentalization in domains such as TADs (topologically associated domains), 49,50 which have been recently shown to be correlated with regions of differential chromatin accessibility 51 . An exploration of this idea may provide a direction for new studies.…”
Section: Discussioncontrasting
confidence: 65%
“…It is well known that both during immune cell differentiation and B or T cell activation, DNA methylation combined with the transcription factors play a vital role in the regulation of gene expression (78), which through DNA methylation of cytosines in the context of cytosineguanine dinucleotides (CpG), often located in clusters (CpG islands) within regulatory regions such as promoters and enhancers. Epigenetics is also thought to be essential for V(D)J rearrangement, and immunological memory (79,80) and recent studies have identified DNA methylation alterations in common variable immunodeficiency (CVID) (78), the Immunodeficiency, Centromere instability and Facial anomalies (ICF) (81,82) and ATM deficiency (83).…”
Section: Epigeneticsmentioning
confidence: 99%
“…The DNA segment connecting two adjacent nucleosomes is referred to as a linker. Nucleosome positioning is critical to various biological processes, primarily because this precise positioning modulates the accessibility of underlying genomic sequence to DNA-binding proteins to regulate transcription (Liu M. et al , 2015; Schones et al , 2008; Tilgner et al , 2009; Whitehouse et al , 2007), genetic replication (Eaton et al , 2010; Liu et al , 2017; Vasseur et al , 2016), and recombination (Pulivarthy, 2016; Smagulova et al , 2011). Therefore, the identification of nucleosome positioning along genomic sequences may allow an in-depth understanding of various biological outcomes.…”
Section: Introductionmentioning
confidence: 99%